2001
DOI: 10.1029/2000gc000080
|View full text |Cite
|
Sign up to set email alerts
|

Birth, death, and resurrection: The life cycle of suprasubduction zone ophiolites

Abstract: [1] Abstract: Suprasubduction zone (SSZ) ophiolites display a consistent sequence of events during their formation and evolution that suggests that they form in response to processes that are common to all such ophiolites. This sequence includes the following: (1) birth, which entails the formation of the ophiolite above a nascent or reconfigured subduction zone; this stage is typically characterized by the eruption of arc tholeiite lavas and the formation of layered gabbros and sheeted dike complex; (2) youth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
281
0
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 455 publications
(300 citation statements)
references
References 181 publications
(272 reference statements)
14
281
0
5
Order By: Relevance
“…Fracture zones separating oceanic lithosphere of different ages and densities are the most plausible sites for subduction initiation (Stern and Bloomer, 1992;Casey and Dewey, 1984;Hawkins et al, 1984;Leitch, 1984). The initiation of subduction starts in response to convergence due to major plate re-organizations (Shervais, 2001;Casey and Dewey, 1984;Hawkins et al, 1984). Stern and Bloomer (1992) suggested that old dense lithosphere sinking into the asthenosphere rolls back and leaves a gap that is filled by rapid spreading at the leading edge of the lithosphere in the upper plate.…”
Section: Discussionmentioning
confidence: 99%
“…Fracture zones separating oceanic lithosphere of different ages and densities are the most plausible sites for subduction initiation (Stern and Bloomer, 1992;Casey and Dewey, 1984;Hawkins et al, 1984;Leitch, 1984). The initiation of subduction starts in response to convergence due to major plate re-organizations (Shervais, 2001;Casey and Dewey, 1984;Hawkins et al, 1984). Stern and Bloomer (1992) suggested that old dense lithosphere sinking into the asthenosphere rolls back and leaves a gap that is filled by rapid spreading at the leading edge of the lithosphere in the upper plate.…”
Section: Discussionmentioning
confidence: 99%
“…Light gray shading represents extent of Eurasian continental crust in our model. central NeoTethys [Hafkenscheid et al, 2006;Pearce et al, 1981;Shervais, 2001;Stampfli and Borel, 2002]. Cessation of arc-magmatism along the Kohistan-Ladakh arc at $61 Ma can be interpreted as the onset of ophiolite emplacement onto Greater India [Khan et al, 2009], while further east the Zedong Ophiolite was likely to have been emplaced at $57 Ma [Ali and Aitchison, 2008].…”
Section: Pre-collision Marginsmentioning
confidence: 99%
“…7B1) and at the same time show HFSE negative anomalies (Fig. 7A1) which are unique characteristics of MORBs with arc signatures (Shervais 2001). Surprisingly, although the LREE depletion in the medium-Ti basalts is more pronounced they display considerably higher relative depletion of Ta-Nb thus confronting MORB and SSZ signatures in one single geochemical group.…”
Section: Tectonomagmatic Significance Of Tholeiitic Basaltsmentioning
confidence: 96%
“…These composite blocks give strong evidence for the "stage of birth" from the geodynamic model of SSZ ophiolites proposed by Shervais (2001). Stern (2004) thought that such association of extrusive rocks were formed by extensive magmatism in the extensional proto-arc-fore-arc basin that spreads over the still active subducting ridge.…”
Section: Tectonomagmatic Significance Of Tholeiitic Basaltsmentioning
confidence: 99%